Cytomegalovirus retinitis after the initiation of highly active antiretroviral therapy: a 2 year prospective study. - Mitchell,SM; Membrey,WL; Youle,MS; Obi,A; Worrell,S; Gazzard,BG (Br J Ophthalmol, 1999)
BACKGROUND/AIMS: There have been several recent reports suggesting that the natural history of cytomegalovirus retinitis (CMVR) has been significantly modified with the development of highly active antiretroviral therapy (HAART). This 2 year prospective cohort study assesses the effect of HAART on the incidence and progression of CMV retinitis in patients with CD4 cell counts below 50 cells x10(6)/l. METHODS: 63 patients, with CD4 cell counts below 50 cells x10(6)/l, who were recruited to a 2 year prospective cohort study at the commencement of combination antiretroviral therapy including the use of the proteinase inhibitor, indinavir, were reported. The response to HAART was assessed in terms of a rise in the CD4 cell count and fall in HIV viral load. An experienced ophthalmologist performed dilated funduscopy at the time of recruitment and thereafter at 2 weekly intervals and retinal photography was performed at monthly intervals in patients with CMVR. The activity and progression of CMV retinitis was assessed on the basis of the characteristic clinical and photographic findings. RESULTS: 34 patients achieved at least 50 CD4 cells x10(6)/l at 3 months after initiation of therapy. New diagnoses of CMVR were seen only in the non-responder group (p=0. 085). Overall, the relative risk of a new retinitis event in this group was 3.52 (95% CI 1.16, 10.68) at 3 months compared with those patients who were responsive to HAART. 12 of the 63 patients had previous CMVR. Disease progression was associated with non-response to therapy (p=0.182 exact). In patients with CMVR the median time to first progression was 18 days (95% CI 8, 91) in non-responders and 121 days (95% CI 0.59, 3.65) in responders. By the end of the 2 year follow up period all surviving patients had >50 CD4 cells x10(6)/l. No CMV events were seen after 8 months of therapy in either group of patients. CONCLUSIONS: These findings suggest that significant clinical immunorestoration to CMV occurs in response t